A preliminary mechanistic test of the effects of light therapy in bulimia nervosa. (1st September 2016) - De Young, Kyle P.; Thiel, Alexandra; Goodman, Erica L.; Murtha-Berg, Erin; Johnson, Nicole K.
ABSTRACT: Negative affect is an important antecedent of binge eating episodes in bulimia nervosa (BN). A small number of studies have found that bright light therapy (BLT) decreases negative affect and binge eating frequency in BN. This study tested whether decreases in the frequency of binge eating in BN during BLT are accounted for by changes in negative affect. Participants ( N = 9) with BN participated in a 6-week within-subjects trial of BLT, making daily ratings of the occurrence of eating disorder behaviours and negative affect, and resulting in 242 participant-days of data. They also completed an assessment battery on four occasions: baseline, pre-intervention, post-intervention, and 2-week follow-up. Use of the therapy light was associated with decreased likelihood of binge eating and lower negative affect; however, the likelihood of binge eating was not entirely accounted for by changes in negative affect. Future research should continue to investigate possible mechanisms through which BLT may influence binge eating in BN.